your weight on the moon is about 1/6 of your weight on earth write and solve an equation to show how much a person weighs on earth if he weighs 16 pounds on the moon.how could you check that your answer is reasonable

Answers

Answer 1
Answer: 16 * 6 = x. 

If one sixth of your weight is 16, multiply it by 6. 

16 x 6 = 96.
Answer 2
Answer:

Final answer:

To find a person's weight on earth when you know their weight on the moon, multiply the moon weight by 6 (since weight on the moon is 1/6 of weight on earth). Therefore, if a person weighs 16 pounds on the moon, they would weigh 96 pounds on earth.

Explanation:

The question asks how much a person weighs on earth if he weighs 16 pounds on the moon. The fact that a person weighs about 1/6 on the moon than on earth would indicate that weight on earth is larger. In this case, you can find the earth weight by multiplying the moon weight to 6 (since it is 1/6). So, using this formula, if a person weighs 16 pounds on the moon, he would weigh 16 * 6 = 96 pounds on earth.

To check if this is reasonable, if you have the earth weight, you can divide by 6 to see if you return to the original moon weight. In this case, 96 / 6 = 16, which is the given moon weight, so the answer seems reasonable.

Learn more about Weight Conversion here:

brainly.com/question/11429990

#SPJ2


Related Questions

What is 80% of 38 ? plzzzz help
to multiply a number by 12, Carter likes to multiply the number by 10 and then multiply it by 2 and add the product. Write an expression with parenthesis how carter would solve 12×16
Tickets to a concert cost $2 for children and $5 for adults. If 630 people attended the concert and the ticket sales totaled $2,910, how many children attended the concert?
Solve 10^6x=93. round to the nearest ten thousand.A) 11.8109 B) 1.0986 C) 13.3801 D) 0.3281
Factor completely, the expression: 2x^3-2x^2-12x

Which expression represents the factored form of 6x^2 - 13x - 5?a) (2x + 5) (3x - 1)
b) (2x- 5) (3x + 1)
c) (6x-5) (x + 1)
d) 6x + 1) (x - 5)

Answers

For the quadratic trinomial ax^2+bx+c the following formula

ax^2+bx+c=a(x-x_1)(x-x_2), where x_1, x_2 are trinomial roots, holds.

1. For trinomial 6x^2 - 13x - 5 find the roots:

.

2. The factoring form is

6x^2-13x-5=6\left(x+(1)/(3)\right)\left(x-(5)/(2)\right) =(3x+1)(2x-5)

Answer: correct option is B.

to FL and add
multiply first terms and multiply last terms and add and see if we get the middle term
example
(x+2)(2x-3)=2x^2+x-6x
2*2x+x*-3=4x-3x=x=middle term so



a. (2x+5)(3x-1)
2x*-1+5*3x=-2x+15x=13x, no we want -13x

b. (2x-5)(3x+1)
2x*1+-5*3x=2x-15x=-13x correct



answer is B

Find the angle measure that makes the statement true. Sin 25° = Cos ____ °

Answers

Since the sine and cosine functions are cofunctions, they are complementary. The format for this is that sinx=cos(90-x). This works for secant and cosecant and tangent and cotangent. So, sin25°=cos65°.

How do you estimate the following question

32 x 43

Answers

Just round it off to the nearest ten or five, like 30*45.Or, round them both to the nearest ten, like 30*40.But, the first one is more accurate.

Jim has gotten scores of 99 and 93 on his first two tests. what score must he get on his third test to keep an average of 90 or greater

Answers

Jim must get  ≥ 78 score to maintain his average  ≥ 90 .

What is an average ?

Every thing has a central tendency , Average is one of the measure of Central Tendency.

It is the mean of all the given numbers and is determined by summing all the numbers or data and then dividing by the total number of data.

It is given that

Jim has gotten scores of 99 and 93 on his first two tests.

He has to maintain an average of 90 or greater

The third test score = ?

Average = (99+93+x)/3

90≤ (99+93+x)/3

270 ≤ (99+93+x)

270 ≤ 192 + x

Therefore x ≥ 78

Jim must get  ≥ 78 score to maintain his average  ≥ 90 .

To know more about Average

brainly.com/question/24057012

#SPJ2

For the average to be 90,

(99 + 93 + x) / 3 = 90

or 192 + x = 270
or x = 270 - 192 = 78

Jim must score at least 78 in the third test.

Find the slope for y = -x - 5 in slope intercept form

Answers

Answer:

Use the slope-intercept form to find the slope and y-intercept.

Slope: −1   y-intercept: (0,−5)

Step-by-step explanation:

If y is the principal square of root 5,what must be true

Answers

y must be a positive integer. 
Hope this was the answer you were looking for!
If it's going to be true y needs to be a positive integer
Hope that's right